2014
DOI: 10.1007/s13187-014-0621-2
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t Know” and Accuracy of Breast Cancer Risk Perceptions Among Appalachian Women Attending a Mobile Mammography Program: Implications for Educational Interventions and Patient Empowerment

Abstract: Risk perceptions are motivating factors for engaging in preventive health behaviors. Yet, almost one third of women attending a mobile mammography program targeted to rural and medically underserved Appalachian women respond “don’t know” to their perceived 5-year risk of breast cancer. This study used cross-sectional data from women aged ≥40 years participating in Bonnie’s Bus Mammography Screening and Preventive Care Survey from 2009 to 2011 to identify factors associated with “don’t know” responses and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Numerous studies mention the influence of education [19]. Apart from education, other significant factors which increase knowledge about breast cancer include: age, marital status, level of income, type of insurance, and having a family member suffering from a tumour disease [11,20]. These relationships have not been observed among the Polish population [21].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies mention the influence of education [19]. Apart from education, other significant factors which increase knowledge about breast cancer include: age, marital status, level of income, type of insurance, and having a family member suffering from a tumour disease [11,20]. These relationships have not been observed among the Polish population [21].…”
Section: Discussionmentioning
confidence: 99%
“…All 10 studies indicated that women who used mobile mammography clinics were from underserved groups. Most studies reported that users of mobile mammography identified as African American (48%–62%) or Hispanic (4%–11%) ( 13 , 14 , 16 , 17 , 19 ), had incomes below $25,000 ( 13 , 15 , 18 , 21 ), and/or were uninsured ( 14 16 , 18 20 ). One study documented use of mobile mammography by American Indians residing in the Northern Plains ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that only 12% to 34% of mobile mammography users had had a screening mammogram in the past year ( 14 , 18 ). Four studies found that 40% to 48% of mobile mammography users adhered to 2-year screening guidelines ( 15 , 18 , 20 , 21 ). Another study documented that only 29% of mobile mammography users had completed a screening mammogram within the past 5 years ( 16 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are wellestablished criteria for acceptable mammographic positioning and quality from the ACR and FDA [1][2][3][4][5] and numerous mobile mammography programs in the United States and abroad [6][7][8][9][10][11][12][13][14][15], to the best of our knowledge there is no published study regarding the effectiveness of technologist training programs abroad on mobile mammographic image quality.…”
Section: Introductionmentioning
confidence: 99%